University personnel and students’ perspective on COVID-19 vaccine acceptability - Jomell Miranda Santiago; Angelo Reyes Santos (International Journal of Public Health Science (IJPHS), 2022)
Vaccines are life-saving technology that has led to the eradication, containment, or control of infectious illnesses around the globe. Many factors affect the vaccine acceptability of an individual. Thus, this study was conducted to determine the coronavirus disease 2019 (COVID-19) vaccine acceptability and the willingness of the students, faculty and staff of Nueva Ecija University of Science and Technology (NEUST) to get vaccinated. A descriptive study approach and total sampling were adopted. A questionnaire was constructed to collect data on the respondents' profile, their source of information and statements regarding their acceptability and willingness to get vaccinated by the COVID-19 vaccine. Informed consent and permission to conduct were acquired. Various statistical tools were used to analyze the data. The vaccine acceptability was generally high and most was willing to get vaccinated. Their primary source of information was from television and social media on the internet. Their willingness to get vaccinated was influenced by their age, gender and the group where they belong in the university. Although more respondents are willing to get vaccinated, some still do not want to get vaccinated. Therefore, health education campaigns and vaccine promotion should be conducted to improve vaccine acceptance during the roll-out of the COVID-19 vaccine.